2014
DOI: 10.1155/2014/384271
|View full text |Cite
|
Sign up to set email alerts
|

Primary Aspergillosis of Bilateral Laryngoceles

Abstract: Laryngocele is an abnormal dilatation of the saccule of laryngeal ventricle, which is usually unilateral and filled with air or fluid. We present a case of bilateral laryngoceles colonized by Aspergillus species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This is the first report of primary laryngeal aspergillosis in a SOT recipient. After an extensive review of the literature, we found other 35 cases of primary laryngeal aspergillosis that have been published in patients with different immune states . We summarize relevant features in Table .…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report of primary laryngeal aspergillosis in a SOT recipient. After an extensive review of the literature, we found other 35 cases of primary laryngeal aspergillosis that have been published in patients with different immune states . We summarize relevant features in Table .…”
Section: Introductionmentioning
confidence: 99%